The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/jgc.2019.32
|View full text |Cite
|
Sign up to set email alerts
|

School Counsellors’ Job Satisfaction: What is the Role of Counselling Self-Efficacy, Trait Anxiety and Cognitive Flexibility?

Abstract: The aim of the present study is to investigate the role of counselling self-efficacy, trait anxiety and cognitive flexibility in predicting job satisfaction of school counsellors. The study was conducted according to a correlational research design. The sample group consisted of 99 female and 77 male school counsellors voluntarily participating in the study. Data collection tools included the Personal Information Form, Job Satisfaction Scale, Counselor Activity Self-Efficacy Scale, Trait Anxiety Inventory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
(87 reference statements)
2
7
0
1
Order By: Relevance
“…But the hypothesis is accepted. This finding is in line with the findings presented by Aydin & Odaci, (2022). The findings show that job satisfaction was identified to have moderate significant correlations with counselling self -efficacy.…”
Section: Discussion and Limitation Of Studysupporting
confidence: 92%
“…But the hypothesis is accepted. This finding is in line with the findings presented by Aydin & Odaci, (2022). The findings show that job satisfaction was identified to have moderate significant correlations with counselling self -efficacy.…”
Section: Discussion and Limitation Of Studysupporting
confidence: 92%
“…Antecedentes investigativos apoyan las hipótesis a contrastar que proponen que la satisfacción laboral de los consejeros escolares tiene correlaciones significativas moderadas con la autoeficacia de la consejería, la ansiedad por rasgos y la flexibilidad cognitiva (Aydin & Odaci, 2020). En esa misma línea los académicos de instituciones de educación superior de Hong Kong, se predijo estadísticamente la insatisfacción laboral, tanto directa como indirectamente, a través de la autoeficacia académica en la investigación y la docencia, estableciendo un vínculo significativo entre los campos de la psicología, la educación superior y el desarrollo profesional (Zhang et.…”
Section: Introductionunclassified
“…A classic definition of job satisfaction (Locke, 1976) includes the positive subjective experience of a person in relation to experiences at work, and it is influenced by various factors. Various external factors, such as demographic characteristics, income, work conditions, schedule, workspace flexibility, work-family enrichment as well as conflict between work and family duties have been associated with job satisfaction in various professions, including teaching professions (Ray & Pana-Cryan 2021, Davidescu, Apostu, Paul, & Casuneanu, 2020Tsakiridou & Kolovou, 2018, Maeran, Pitarelli, & Cangano, 2013, Abendroth & Den Dulk, 2011, McNall, Masuda, & Nicklin, 2010, but an important point of focus would be the research of internal motivators that contribute to the attainment of a good level of positive experience at work, such as cognitive flexibility, self-efficacy (Aydin & Odaci, 2020), loyalty and commitment to work (Sakalli Demirok, 2018), and psychological flexibility (Kuo, Ye, Chen, & Chen, 2017). The importance of the level of satisfaction is high, as a fair level of satisfaction is required in the occupational field, in order for a person to have good performance and efficacy at work (Aydin & Odaci, 2020), in various fields, including education.…”
Section: Introductionmentioning
confidence: 99%
“…Various external factors, such as demographic characteristics, income, work conditions, schedule, workspace flexibility, work-family enrichment as well as conflict between work and family duties have been associated with job satisfaction in various professions, including teaching professions (Ray & Pana-Cryan 2021, Davidescu, Apostu, Paul, & Casuneanu, 2020Tsakiridou & Kolovou, 2018, Maeran, Pitarelli, & Cangano, 2013, Abendroth & Den Dulk, 2011, McNall, Masuda, & Nicklin, 2010, but an important point of focus would be the research of internal motivators that contribute to the attainment of a good level of positive experience at work, such as cognitive flexibility, self-efficacy (Aydin & Odaci, 2020), loyalty and commitment to work (Sakalli Demirok, 2018), and psychological flexibility (Kuo, Ye, Chen, & Chen, 2017). The importance of the level of satisfaction is high, as a fair level of satisfaction is required in the occupational field, in order for a person to have good performance and efficacy at work (Aydin & Odaci, 2020), in various fields, including education. Although there is a concern that teachers, especially those working in special educational settings, may experience high levels of distress and burnout, some authors (Darcy, Kusznikow, & Lester, 1995) found no significant differences regarding the overall job satisfaction level between teachers working in special education and teachers in regular settings.…”
Section: Introductionmentioning
confidence: 99%